Is There a Benefit to Modularity in 'Simpler' Femoral Revisions?. Issue 2 (February 2016) - Huddleston, James I.; Tetreault, Matthew W.; Yu, Michael; Bedair, Hany; Hansen, Viktor J.; Choi, Ho‐Rim; Goodman, Stuart B.; Sporer, Scott M.; Della Valle, Craig J.
Abstract: Background: Modular revision femoral components allow the surgeon to make more precise intraoperative adjustments in anteversion and sizing, which may afford lower dislocation rates and improved osseointegration, but may not offer distinct advantages when compared with less expensive monoblock revision stems. Questions/purposes: We compared modular and monoblock femoral components for revision of Paprosky Type I to IIIA femoral defects to determine (1) survivorship of the stems; and (2) complications denoted as intraoperative fracture, dislocation, or failure of osseointegration. Methods: Between 2004 and 2010, participating surgeons at three centers revised 416 total hip arthroplasties (THAs) with Paprosky Type I to IIIA femoral defects. Of those with minimum 2‐year followup (343 THAs, mean followup 51 ± 13 months), 150 (44%) were treated with modular stems and 193 (56%) were treated with monoblock, cylindrical, fully porous‐coated stems. During this time, modular stems were generally chosen when there was remodeling of the proximal femur into retroversion and/or larger canal diameters (usually > 18 mm). A total of 27 patients died (6%) with stems intact before 2 years, 46 THAs (13%) were lost to followup before 2 years for reasons other than death, and there was no differential loss to followup between the study groups. The modular stems included 101 with a cylindrical distal geometry (67%) and 49 with a tapered geometry (33%). Mean age (64 versus 68 years), percentage of women (53% versus 47%), and body mass index (31 versus 30 kg/m 2 ) were not different between the two cohorts, whereas there was trend toward a slightly greater case complexity in the modular group (55% versus 65% Type 3a femoral defects, p = 0.06). Kaplan‐Meier survivorship was calculated for the endpoint of aseptic revision. Proportions of complications in each cohort (dislocation, intraoperative fracture, and failure of osseointegration) were compared. Results: Femoral component rerevision for any reason (including infection) was greater (OR, 2.01; 95% CI, 1.63‐2.57; p = 0.03) in the monoblock group (27 of 193 [14%]) compared with the modular cohort (10 of 150 [7%]). Femoral component survival free from aseptic rerevision was greater in the modular group with 91% survival (95% CI, 89%‐95%) at 9 years compared with 86% survival (95% CI, 83%‐88%) for the monoblock group in the same timeframe. There was no difference in the proportion of mechanically relevant aseptic complications (30 of 193 [16%] in the monoblock group versus 34 of 150 [23%] in the modular group, p = 0.10; OR, 1.47; 95% CI, 0.86‐2.53). There were more intraoperative fractures in the modular group (17 of 150 [11%] versus nine of 193 [5%]; OR, 2.2; 95% CI, 1.68‐2.73; p = 0.02). There were no differences in the proportions of dislocation (13 of 193 [7%] monoblock versus 14 of 150 [9%] modular; OR, 0.96; 95% CI, 0.67‐1.16; p = 0.48) or failure of osseointegration (eight of 193 [4%] monoblock versus three of 150 [2%] modular; OR, 1.92; 95% CI, 0.88‐2.84; p = 0.19) between the two groups with the number of hips available for study. Conclusions: Although rerevisions were less common in patients treated with modular stems, aseptic complications such as intraoperative fractures were more common in that group, and the sample was too small to evaluate corrosion‐related or fatigue concerns associated with modularity. We cannot therefore conclude from this that one design is superior to the other. Larger studies and pooled analyses will need to be performed to answer this question, but we believe modularity should be avoided in more straightforward cases if possible. Level of Evidence: Level III, therapeutic study.